ROLE OF HERBAL DERIVATIVES IN THE MANAGEMENT OF ORAL SUBMUCOUS FIBROSIS - R.P, SHRUTHI; A, AMUDHAN; FATHIMA.H, AAFREEN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Oral submucous fibrosis (OSMF) is a cancerous condition affecting oral cavity with a higher rate of malignant transformation. It is a chronic debilitating disease affecting the oral mucosa as well as oropharynx. There are numerous therapy options available, such as antioxidants, corticosteroids, nutritional supplements to surgical management in advance stages of OSMF. The utilization of medicinal and aromatic plants has gained increasing attention in recent years, with new concepts as they have demonstrated a wide range of therapeutic potential, including anti-inflammatory, immunomodulatory, and antioxidant properties. Herbal medicines include the crude or unrefined products of plants, or herbal medicines produced from plants containing concentrated or purified herbal ingredients The properties of herbal derivative medicine such as antioxidant, anti-inflammatory and analgesic effects that may be crucial in mitigating the underlying inflammatory and fibrotic processes associated with oral submucous fibrosis. This narrative review will elaborate on the various traditionally used herbal medicines and their role in the management of OSMF